Aggregate lending standards and inequality - Vanessa Schmidt; Hannah Magdalena Seidl (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
We study the effects of movements in aggregate lending standards on macroeconomic aggregates and inequality. We show in a New Keynesian model with heterogeneous households and housing that a looser loan-to-value (LTV) ratio stimulates housing demand, nondurable consumption, and output. Our model implies that the LTV shock transmits to macroeconomic aggregates through higher household liquidity and a general-equilibrium increase in house prices and labor income. We also show that a looser LTV ratio redistributes housing wealth from the top 10% of the housing wealth distribution to the bottom 50%, indicating an overall decrease in inequality.
Keywords: E12; E21; E44; E52; 330; Heterogeneous Agents; Incomplete Markets; Housing; Macroprudential Policies